7 - Legal Educational Platforms and Disciplines of the Future - Cheka, Cosmas (Journal of Higher Education in Africa, 2022)
Provision of quality education has become a leading challenge in the world today. In 2005, world university population was 138 million. In Cameroon’s state universities, the student population of the universities of Yaoundé University II and Ngaoundéré for example, was respectively some 27,000 and 23,000 in 2017/18. These numbers pose problems of cost, geography, infrastructure and educational delivery platforms that the confines of traditional university and its departments cannot accommodate. This article attempts a definition of the legal educational platforms and the disciplines of the future in Cameroon. The article was prepared through a combination of archival and internet search, and expert consultation. Archival and Internet research was carried out through an analysis of the existing literature in the domains of web technologies, online learning courseware, robotics and artificial intelligence (AI) as well as of legal disciplines and delivery platforms. Expert consultation was attained through qualitative interviews and exchanges with university administrators. The results show that web technologies, the Internet, MOOC, edX and Coursera hold solutions to some of the problems of platforms. Robotics and AI now enhance courseware delivery while dictating where policy, legal disciplines and the law should go. Robotics and AI have also disrupted the concept of ‘labour’ and ‘rights’. Similarly, machines and AI rely on personal and corporate data to function but attacks on network confidentiality, availability and integrity have given birth to new legal disciplines such as the laws of cyberwarfare, data-governance, digital intellectual property, e-commerce and electronic contracts.